Navigating the Hemodynamic Paradox: Integrated Nursing Management of Cardiogenic Shock Complicated by Acute Gastrointestinal Fluid Loss - Fuad Alfian Nurfahmi; Dwi Yoga Setyarini; Nurul Arifah; Ikha Nurjihan; Yopi Darmawan (Health and Technology Journal (HTechJ), 2026)
Cardiogenic shock is a life-threatening cardiovascular emergency characterized by profound systemic hypoperfusion and multi-organ dysfunction. This case study delineates the clinical trajectory of a 75-year-old female presenting with progressive dyspnoea, generalized weakness, and acute gastrointestinal distress manifesting as severe diarrhea. Clinical investigations revealed severe tachypnoea (50 breaths per minute), hypotension, cardiomegaly, and bilateral suprahilar pulmonary edema, establishing a diagnosis of cardiogenic shock secondary to rapid atrial fibrillation. Primary nursing diagnoses included an ineffective breathing pattern, activity intolerance, and diarrhea, prompting immediate collaborative therapeutic interventions. The deployed regimen encompassed intensive respiratory monitoring, strategic semi-Fowler positioning, high-flow oxygen therapy (8 L/min), structured energy management, and meticulously titrated intravenous fluid resuscitation. Following 72 hours of targeted nursing care, the patient demonstrated optimal clinical outcomes, evidenced by a normalized respiratory rate (20 breaths per minute), stabilized oxygen saturation (98%), complete resolution of diarrhea, and restored physical tolerance. The unique clinical challenge in this case involved the intricate intersection of cardiogenic respiratory failure and profound gastrointestinal fluid loss, which severely complicated conventional fluid titration protocols. This report validates an integrated nursing protocol that successfully coordinates non-invasive oxygenation strategies with precise metabolic and fluid stabilization. Rapid execution of structured positioning and tailored oxygenation bundles significantly mitigates myocardial workload and improves clinical outcomes in acute cardiac crises.